Pengaruh Kompetensi dan Motivasi terhadap Kinerja Karyawan Sumber Daya Mandiri Muara Teweh Di Kalimantan Tengah - Endang Murti; Sulastini Sulastini; Siti Rusidah (JURNAL BISNIS DAN PEMBANGUNAN, 2015)
This study berjutuan to the effect of competence (X1) and motivation (X2) on employee performance (Y). Samples were determined by 69 people who are saturated sample / census. techniques of data collection using the questionnaire. and the analysis of data using multiple linear regression.The test results prove the existence of significant influence variables simultaneously competence and motivation variable with a contribution of 88.7%. Partially the influence of motivational variables on the performance of the employee contributions of 68%, the variable competence is the dominant contribution to the performance of employees with a contribution of 74%..Keywords: competence, motivation, performance.